Codium tomentosum and Plocamium cartilagineum: Chemistry and antioxidant potential - Valentão, Patrícia (2019)
The chemical composition of green Codium tomentosum Stackhouse and red Plocamium cartilagineum (Linnaeus) P.S. Dixon seaweeds from the Atlantic Ocean surrounding Portugal was studied. For the first time, the profile of organic acids was analysed in these matrices: seven and four organic acids were detected in green and red species, respectively. In P. cartilagineum these compounds were present in vestigial amounts, whilst C. tomentosum exhibited a higher content, with oxalic acid being the main compound. Phenolics, UV-absorbing compounds, were absent in both species. Volatiles profile was also determined for the first time and a total of 41 compounds were identified, which included alcohols, aldehydes, esters, halogenated compounds, ketones, monoterpenes (namely terrestrial ones), norisoprenoid derivatives, amongst others. Norisoprenoid derivatives and aldehydes were predominant. The main volatiles in green and red seaweeds were limonene and benzophenone, respectively. Additionally, both species revealed considerable antioxidant activity against both reactive oxygen (superoxide radical) and reactive nitrogen (nitric oxide) species, in a concentration-dependent manner.